The Mediating Role of Reading Ability in the Relationship Between School Facilities and Text Comprehension Among Elementary School Students - Miswati Miswati; Alfroki Martha; Weni Yulastri (Journal of Education Research, 2026)
Text comprehension remains a central challenge in elementary education, as students' capacity to derive meaning from written texts directly shapes their overall academic performance. This study aimed to analyze the effects of reading ability and school facilities on students' text comprehension at SD Negeri 168/III Patok Empat, Kayu Aro Barat District. A quantitative approach with a causal associative design was employed, with all 92 students of the school serving as the study sample. Data were gathered through a standardized reading ability test, a structured school facilities questionnaire, and a text comprehension assessment, then analyzed using simple and multiple linear regression. Results indicated that reading ability exerted a significant and positive effect on text comprehension (β = 0.524; t = 5.82; p < 0.001), as did school facilities (β = 0.498; t = 5.41; p < 0.001). Taken together, the two variables explained 44.8% of the variance in student comprehension scores (F = 36.52; p < 0.001). These findings underscore the importance of simultaneously cultivating reading skills and improving learning infrastructure to optimize text comprehension outcomes in primary schooling.